117k views
2 votes
Given that f(x) = −x + 4 and g(x) = −2x − 3, solve for f(g(x)) when x = 2. (1 point)

(A) −14
(B) −7
(C) 7
(D) 11

2 Answers

3 votes

Answer:

D

Explanation:

I just took the test. Hope this helps

User Prashant Thorat
by
4.6k points
3 votes

Answer:

D

Explanation:

First you need to find which function represents f(g(x)) and then you replace each x in this new function by 2.

f(4), for example, is f when x = 4, right? So f(4) = -4+4 = 0

So, f(g(x)) will represent f when x = g(x). x = g(x) when x = -2x-3

So, f(g(x)) = f(-2x-3) = -(-2x-3) + 4

= -(-2x)-(-3)+4

= 2x + 3 + 4

= 2x + 7

So f(g(x)) = 2x + 7.

Now when x = 2, f(g(x)) = 2*2 + 4 = 11, which is option D.

User Bobe Kryant
by
5.1k points